Somaesthetics and Sport - Edgar, Andrew, (Studies in Somaesthetics ;, 2022)
Somaesthetics and Sport brings together a diverse set of explorations into the embodied experience of watching and playing sport. Sport can at once be a source of sensual beauty and pleasure, and also of pain and anguish; spectators can both celebrate and glorify athletes, but also expect certain forms of behaviour, and intentionally or otherwise police the movements of their bodies; sport and physical exercise can improve our health and increase the self-awareness of our abilities and limitations, but they also help us to shape our sense of what it means to live a good life.